2021
DOI: 10.1002/chem.202100089
|View full text |Cite
|
Sign up to set email alerts
|

Uranium versus Thorium: Synthesis and Reactivity of [η5‐1,2,4‐(Me3C)3C5H2]2U[η2‐C2Ph2]

Abstract: The synthesis, electronic structure, and reactivity of a uranium metallacyclopropene were comprehensively studied. Addition of diphenylacetylene (PhC≡CPh) to the uranium phosphinidene metallocene [η5‐1,2,4‐(Me3C)3C5H2]2U=P‐2,4,6‐tBu3C6H2 (1) yields the stable uranium metallacyclopropene, [η5‐1,2,4‐(Me3C)3C5H2]2U[η2‐C2Ph2] (2). Based on density functional theory (DFT) results the 5f orbital contributions to the bonding within the metallacyclopropene U‐(η2‐C=C) moiety increases significantly compared to the rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 128 publications
0
18
0
Order By: Relevance
“…A more elegant approach relies on well-defined organometallic actinide compounds, that do not possess a divalent oxidation state but serve as An­(II) synthons in the presence of suitable substrates. This allows the reactivity of An­(II) compounds to be evaluated, while evading the synthetic challenges associated with these difficult to access oxidation states . Redox-active ligands with energetically relatively low-lying acceptor orbitals such as 2,2′-bipyridine, 1,4-diazabutadiene, pyridine diimine, and arenes are particularly well suited for the latter approach since they may “store” or deliver electrons when needed.…”
Section: Introductionmentioning
confidence: 99%
“…A more elegant approach relies on well-defined organometallic actinide compounds, that do not possess a divalent oxidation state but serve as An­(II) synthons in the presence of suitable substrates. This allows the reactivity of An­(II) compounds to be evaluated, while evading the synthetic challenges associated with these difficult to access oxidation states . Redox-active ligands with energetically relatively low-lying acceptor orbitals such as 2,2′-bipyridine, 1,4-diazabutadiene, pyridine diimine, and arenes are particularly well suited for the latter approach since they may “store” or deliver electrons when needed.…”
Section: Introductionmentioning
confidence: 99%
“…[38] Later, they also found that the comparable uranacyclopropene 7 b could undergo similar insertion of nitrile to afford azauranacyclopentadiene 8 b. [40] Interestingly, when more sterically encumbered nitriles, such as CyCN and Ph 2 CHCN were employed, the alkyne dissociation and nitrile-nitrile coupling occurred to give the diazauranacyclopentadienes. In 2021, we reported the reaction of lutetacyclopropene 9 towards nitriles to give azalutetacyclopentadienes 10.…”
Section: Synthesis Of Azametallacyclopentadienesmentioning
confidence: 99%
“…For example, when the reaction between uranacyclopropene 8 b and benzyl nitrile (PhCH 2 CN) was conducted, uranacyclic enamine 15 was obtained, instead of azauranacyclopentadiene 14. [40] The formation of 15 probably proceeds through the insertion of PhCH 2 CN into the UÀ C(sp 2 ) bond of 8 b to give 14, and the following tautomerization via intramolecular 1,3-H shift providing 15 (Scheme 3b). Similarly, the reactions of lutetacyclopropene 9 towards one equiv.…”
Section: Hydrolysis Iodination and Proton Transfer Reactionsmentioning
confidence: 99%
“…To realize the assembly of two nitriles into diazametallacyclopentadienes, a suitable two-electron reductant of rare-earth species should be considered. [19][20][21][22][23]33,34 Because of the strong reducing ability of the reduced naphthalene ligand, the reduced naphthalene complexes of rare-earth metals were deemed as the precursors. [35][36][37][38][39][40][41][42][43][44] Herein, the selective C-C coupling of nitriles promoted by rare-earth metal reduced naphthalene complexes G was realized, affording the first rare-earth diazametallacyclopentadienes D via azametallacyclopropene intermediates I (Scheme 1c).…”
Section: Introductionmentioning
confidence: 99%